PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING BERBANTUAN MEDIA VISUAL UNTUK MENINGKATKAN KREATIVITAS DAN HABITS OF MIND MATEMATIS SISWA PADA KELAS X MA AL-KAUTSAR NW REBAN BURUNG TAHUN PELAJARAN 2018/2019 - Muzaki, Ahmad; Solihatton, Solihatton; Yuntawati, Yuntawati (Universitas Pendidikan Mandalika (UNDIKMA), 2018)
The low of student learning outcomes in mathematics subjects is caused by a lack of student involvement and the conventional methods used by the teacher. Therefore the need for creativity and mathematical habits of mind to be able to improve learning outcomes. To improve creativity and mathematical habits of mind, learning methods are needed that can stimulate student’s creativity and mathematical habits of mindwith Creative Problem Solving (CPS)models assisted by visual media. The aims of this study was to determine the increase in student’s creativity and mathematical habits of mindby applying CPS models assisted by visual media in grade X MA Al-Kautsar NW RebanBurung Academic Year 2018/2019. This type of research was classroom action research conducted in two cycles. In the first cycle obtained the level of creativity of students was 2.78, and for the percentage of students' mathematical habits of mind was 63.63%, and the percentage of classical completeness was 75%. While in the second cycle there was an increase in the level of student creativity to 3.07, and for the percentage of students mathematical habits of mind increased to 82.25%, the percentage of classical completeness reached 95% and had fulfilled the KKM.